Ethnobotany of postnatal herbal medicine of the Malay community of Ketapang as a source of culture-based biology learning - Siti Kurnia Wulan; Anandita Eka Setiadi; Ari Sunandar (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2025)
Along with the development of health services and the use of modern medicine led to the loss of knowledge of medicinal plants for postnatal herbs. The purpose of this study was to determine the kinds of herbal medicine, plants used by the Ketapang Malay Community in Natai Kuini village, and the ethnobotanical potential of postnatal herbal medicine plants as a learning resource. This research uses an exploratory descriptive method with a qualitative approach where researchers divide the 2 stages of research from plant data collection and postnatal herbs by interview and observation. The interview used snowball sampling technique. Further data collection is in the form of questionnaire results of potential learning resources. The results of the study found 27 spesies of plants and 15 types of postnatal herbs. Potential learning resources aspects of the clarity of potential 95.31%. Aspects of target clarity 97.92%, suitability of objectives 97.92%, feasibility of exploration guidelines 97.92%, clarity of information revealed score 90.63%, clarity of expected results 90.63% and interpretation of ‘very good’ with an average presentation of 95.06%. This research has a scientific impact on education by providing new insights into the ethnobotanical potential of postpartum herbal plants as an effective learning resource, especially in the context of biodiversity and classification of living things for Class X students.Abstrak. Seiring dengan berkembangnya pelayanan kesehatan dan penggunaan obat modern menyebabkan hilangnya pengetahuan terhadap tumbuhan obat untuk jamu pasca melahirkan. Tujuan penelitian ini untuk mengetahui macam-macam jamu, tumbuhan yang digunakan Masyarakat Melayu Ketapang didesa Natai Kuini, dan potensi etnobotani tumbuhan jamu pasca melahirkan sebagai sumber belajar. Penelitian ini mengunakan metode deskriptif eksploratif dengan pendekatan kualitatif dimana peneliti membagi 2 tahap penelitian dari pengambilan data tumbuhan dan jamu pasca melahirkan dengan wawancara dan observasi. Wawancara menggunakan teknik snowball sampling. Pengambilan data selanjutnya berupa hasil angket potensi sumber belajar. Hasil penelitian ditemukan 27 jenis tumbuhan dan 15 jenis jamu pasca melahirkan. Potensi sumber belajar aspek dari kejelasan potensi 95.31%. Aspek kejelasan sasaran 97.92%, kesesuain tujuan 97.92%, kelayakan pedoman eksplorasi 97.92%, kejelasan informasi yang diungkap skor 90.63%, kejelasan hasil yang diharapkan 90.63% dan interpretasi